2011
DOI: 10.1017/s0007114511005186
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of calcium balance byFructus Ligustri Lucidiextract in mature female rats was associated with the induction of serum parathyroid hormone levels

Abstract: Fructus Ligustri Lucidi (FLL) is a commonly prescribed herb in many kidney-tonifying Traditional Chinese Medicinal formulae for the treatment of osteoporosis. The present study aimed to identify the active fractions in FLL and to characterise its effects on Ca balance, calciotropic hormone levels as well as bone properties in mature female rats fed diets containing different levels of Ca. In the present study, 4-month-old Sprague -Dawley female rats were treated with either FLL ethanol extract (EE), ethyl acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…The present study reported the regulation of FLL on CaSR, even though there is emerging evidence to demonstrate its regulation on calcium-transporting proteins Lyu et al, 2014;Zhang et al, 2008). Thus, the present results provided us with a clue that the potential effects of FLL on CaSR in parathyroid gland need to be further explored to explain the observed increase of serum PTH level as described previously (Dong et al, 2012). In addition, the possibility of FLL as CaSR antagonist should also be studied to show its potential on directly regulating bone metabolism by the increasing PTH level.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The present study reported the regulation of FLL on CaSR, even though there is emerging evidence to demonstrate its regulation on calcium-transporting proteins Lyu et al, 2014;Zhang et al, 2008). Thus, the present results provided us with a clue that the potential effects of FLL on CaSR in parathyroid gland need to be further explored to explain the observed increase of serum PTH level as described previously (Dong et al, 2012). In addition, the possibility of FLL as CaSR antagonist should also be studied to show its potential on directly regulating bone metabolism by the increasing PTH level.…”
Section: Resultssupporting
confidence: 74%
“…After 1 week of recovering from surgery, the ovariectomized (OVX) mice were randomly divided into four groups of eight: vehicle-treated (OVX), FLL-treated (OVX +F ), calcium-fortified (1.0% Ca) milk powder-treated (5 g/mice, OVX + M), and the combination of FLL and milk powder (OVX + FM). FLL was orally administered at dosage of 700 mg/kg as described previously (Dong et al, 2012;Zhang et al, 2008).…”
Section: Animal Treatmentmentioning
confidence: 99%
“…The crude plant was extracted with 70% ethanol, the mixture was filtered and lyophilized to dryness to obtain FLL ethanol extract, which was then suspended in hot water and made into dried powders by a process of evaporation and lyophilisation. The two most prominent peaks in WF-EE were identified to be nuezhenide and salidroside as demonstrated in our previous report (Dong et al, 2012).…”
Section: Water-soluble Fraction Of Fll Ethanol Extract (Wf-ee)supporting
confidence: 71%
“…It was prepared as previously described (Dong et al, 2012). Briefly, Fructus Ligustri Lucidi (FLL) was obtained from Jiangsu province of China.…”
Section: Water-soluble Fraction Of Fll Ethanol Extract (Wf-ee)mentioning
confidence: 99%
See 1 more Smart Citation